Quantification of artemisinin in Artemisia annua extracts by 1H‐NMR - Castilho, Paula C. (2008)
Artemisinin is a polycyclic sesquiterpene lactone that is highly effective against multidrug-resistant strains of Plasmodium falciparum, the etiological agent of the most severe form of malaria. Determination of artemisinin in the source plant, Artemisia annua, is a challenging problem since the compound is present in very low concentrations, is thermolabile and unstable, and lacks chromophoric or fluorophoric groups. The ain of this study was to develop a simple protocol for the quantification of artemisinin in a plant extract using an (1)H-NMR method. Samples were prepared by extraction of leaf material with acetone, treatment with activated charcoal to remove chlorophylls and removal of solvent. (1)H-NMR spectra were measured on samples dissolved in deuterochloroform with tert-butanol as internal standard. Quantification was carried out using the using the delta 5.864 signal of artemisinin and the delta 1.276 signal of tert-butanol. The method was optimised and fully validated against a reference standard of artemisinin. The results were compared with those obtained from the same samples quantified using an HPLC-refractive index (RI) method. The (1)H-NMR method gave a linear response for artemisinin within the range 9.85-97.99 mm (r(2) = 0.9968). Using the described method, yields of artemisinin in the range 0.77-1.06% were obtained from leaves of the A. annua hybrid CPQBA x POP, and these values were in agreement with those obtained using an HPLC-RI.